OCCURRENCE OF TOMATO EARLY BLIGHT DISEASE AND ASSOCIATED ALTERNARIA SPECIES IN PUNJAB, PAKISTAN - H. M. Riaz; S. Chohan; M. Abid (Journal of Animal and Plant Sciences, 2021)
Early blight disease of tomato, triggered by Alternaria species, is one of the destructive diseases of tomato in Pakistan and around the globe. In this study, a survey was conducted during 2016-17 to estimate the early blight disease incidence and severity, and the identification of fungal species associated with the disease from the eight districts in Punjab Province of Pakistan: Gujranwala, Lahore, Multan, Bahawalpur, Sahiwal, Muzaffargarh, Rajanpur and Faisalabad. The disease incidence and severity from the eight districts were further associated with the different environmental variables. Eight Alternaria isolates, representing eight districts, were characterized on morphological basis and the four most pathogenic isolates on molecular (ITS rDNA) basis. The pathogenicity of the most pathogenic isolate was first evaluated by detached leaf assay and then compared with attached leaf assay. Bahawalpur district was found to be the most infected with maximum 75 % disease incidence and Rajanpur was the least affected region with 9% disease incidence while maximum disease severity index was recorded from Multan with 24% and lowest from Rajanpur with 1%. The disease incidence showed positive correlation with relative humidity and negative correlation with temperature while the rainfall and UV showed no influence. Out of four molecularly identified isolates of Alternaria, only one isolate was identified as being A. solani and the remaining three belonged to A. alternata species.A. solani showed the highest (score 3.33) level of pathogenicity over all the A. alternata isolates (0.66-2.66). This study concluded that the early blight disease is of high importance with great prevalence in Pakistan due to highly favorable environment especially relative humidity (55-61 %) and temperature (14-36 °C). Here, two Alternaria species are the main cause of early blight disease and out of them A. alternata is the most common while A. solani is the most pathogenic fungus.
Keywords: Tomato; Early blight disease; Alternaria species; Environmental variables; Pathogenicity